Synthesis and electrochemical characterisation of polypyrrole and novel n-substituted polypyrrole conducting polymers - Patterson, Aileen. (Trinity College (Dublin, Ireland). School of Chemistry, 2004)
In this study the synthesis of novel redox substituted pyrrole monomers was achieved. Subsequent investigations into the electrochemical behaviour of the hybrid monomers and polymers were carried out. The study was to examine the use of these chemically modified electrodes as potential sensors for compounds of biological significance. To this end a total of fifteen novel compounds were synthesized, this included seven new monomer species: [4-(Pyrrol-l-yl)butyl]ferrocene-carboxamide, 18 n=4, [5-(Pyrrol-l-yl)pentyl]ferrocene-carboxamide, 18 n=5, [6-(Pyrrol-lyl) hexyl]ferrocene-carboxamide, 18 n=6 [7-(Pyrrol-lyl)heptyl]ferrocenecarboxamide, 18 n=7, 1,1'-Bis-[5-(Pyrrol-l-yl)pentyl]ferrocene-1,1'-dicarboxam ide, 20 n = 5, 1,1'-Bis-[7-(Pyrrol-l-yl)heptyl]ferrocene-1,1'-dicarboxamide, 20 n=7, and complex 21 were all prepared according to facile, high yielding reaction schemes.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin